Antimicrobial photodynamic therapy for dermatological infections: current insights and future prospects - Almenara-Blasco, M.; Pérez-Laguna, V.; Navarro-Bielsa, A.; Gracia-Cazaña, T.; Gilaberte, Y. (Frontiers in Photobiology, 2024)
Introduction: Light-based antimicrobial photodynamic therapy (aPDT) shows promise against a wide range of microorganisms, including drug-resistant strains, with low resistance development likelihood. However, its limitations include the need for light exposure, suitability for local infections, and limited industry interest. Relevant studies on aPDT for various infections are discussed. Methods: We conducted an extensive literature review on aPDT encompassing articles published from the year 2000 to the current date. To compile comprehensive data, multiple databases (PubMed, Web of Science, Scopus, and Cochrane Library) were systematically searched for relevant studies in both English and Spanish languages. The search strategy involved a combination of Medical Subject Headings (MeSH) terms and free-text terms. The terms included variations and combinations of “Antimicrobial Photodynamic Therapy,” “aPDT,” “photodynamic inactivation,” “microbial photoinactivation,” among others. To ensure the reliability and quality of the information gathered, articles were screened based on relevance to aPDT in antimicrobial therapy, methodological rigor, and alignment with the objectives of this review. Results: aPDT shows promise in treating various cutaneous infections. It effectively targets fungal infections, including caused by dermatophytes and Malassezia spp., with notable results against dermatophytosis and tinea capitis. New photosensitizers, like nanoencapsulated hypericin, hold potential for treating these infections. In onychomycosis, aminolevulinic acid-aPDT or methylene blue-aPDT offers an alternative to conventional therapies, showing cure rates as high as 90%. For bacterial infections, it presents a solution against antibiotic-resistant strains and infected ulcers, with potential benefits for wound healing. Regarding viral infections, it indirectly targets viruses by impacting host cells’ metabolism, showing efficacy against human papillomavirus and herpes viruses. Lastly, aPDT demonstrates success in treating parasitic infections, particularly leishmaniasis, with cure rates of up to 100%. Discussion: aPDT is increasingly used in dermatological infections, showing efficacy against various microorganisms and stimulating wound healing. It can combat resistant strains and mixed infections, especially in chronic wounds. Combining photodynamic therapy with antimicrobials is a promising strategy to address antimicrobial resistance, but there are practical limitations. Further research is needed for home-based protocols, portable devices, and adapting photosensitizers, as aPDT holds potential as an alternative treatment for recalcitrant infections and immunosuppressed patients, though challenges remain in application.